Fermented Formulation of Silybum Marianum Seeds: Optimization, Heavy Metal Analysis, and Hepatoprotective Assessment - Echeverria-Morgado, J (Elsevier GmbH, 2024)
Background: Fermented formulations are extensively used in Ayurveda due to several benefits like improved palatability, bioavailability, pharmacological potential, and shelf life. These formulations can also quench the heavy metals from the plant material and thus reduce the toxicity. Seeds of Silybum marianum (L.) Gaertn. are widely used for the management of many liver diseases. Study design and methods: In the present study, we developed a novel fermented formulation of S. marianum seeds and evaluated parameters like safety (heavy metal analysis) and effectiveness (hepatoprotective). As the developed formulation s validation is crucial, the critical process variables (time, pH, and sugar concentration) are optimized for alcohol and silybin content using the Box-Behnken design (BBD). Results: The response surface methodology coupled with BBD predicted the optimized conditions (fermentation time (28 days), pH 5.6, and sugar concentration (22.04%)) for the development of a fermented formulation of the selected herb. Moreover, the alcohol content (6.5 ± 0.9%) and silybin concentration (26.1 ± 2.1%) were confirmed in optimized formulation by GC–MS and HPTLC analysis. The optimized formulation was also analyzed for heavy metals (Pb, As, Hg, and Cd); their concentration is significantly less than the decoction of herbs. Further, the comparative evaluation of the developed formulation with the marketed formulation also confirmed that the fermented formulation s silybin concentration and percentage release were significantly enhanced. In addition, the developed fermented formulation s percentage recovery of HepG2 cell lines after treatment with CCl4 was significantly improved compared with the marketed formulation. Conclusion: It can be summarized that the developed fermented formulation improves safety and effectiveness compared to other market formulations. Finally, it can be concluded that the developed fermented formulation could be further explored as a better alternative for developing Silybum marianum preparation. © 2023 The Author(s)